An Exploratory Study on the Level of Trust Among Hungarian Food Manufacturer Companies - Erdei, Edina (International Journal of Engineering and Management Sciences, 2020)
The intensification of globalized economic competition is playing an increasingly important role in the lives of companies to determine their true position among their competitors. Food companies are of paramount importance because of their role and weight in the national economy. In Hungary, the food industry plays an important social and economic role and is a world leader in terms of employment and value added. Currently, there are nearly 1100 active food companies in Hungary, so it is worth examining the peculiarities of the role of trust between companies.There are often contradictory statements in the literature about the effects of Industry 4.0 technologies and the trust placed in IT tools. Therefore, it is a relevant research question to examine whether the characteristics of the role of trust - e.g. staff, suppliers, IT tools and technologies, etc. as confidence levels can have a direct positive impact on the efficiency, profits, liquidity, etc. of the companies in question. development.During the research, I analyzed the level of trust between the food trading companies, in which I discuss the trust within the industry within the company. My aim is to further enrich my previous research knowledge in this field.